2016
DOI: 10.1037/pag0000115
|View full text |Cite
|
Sign up to set email alerts
|

Adversity, time, and well-being: A longitudinal analysis of time perspective in adulthood.

Abstract: Despite the prominence of time in influential aging theories and the ubiquity of stress across the lifespan, research addressing how time perspective (TP) and adversity are associated with wellbeing across adulthood is rare. Examining the role of TP in coping with life events over the lifespan would be best accomplished after large-scale population-based exposure to a specific event, with repeated assessments to examine within-and between-person differences over time.A national sample aged 18-91 years (N = 722… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 51 publications
(96 reference statements)
1
37
0
1
Order By: Relevance
“…Interestingly, negative life events were associated with both Past Negative and Future Negative in the correlational analysis (see Table 2). This finding possibly reflects that even though an individual's time perspective is considered as fairly stable and traitlike , it may at least to some extent, be modulated by environmental influences, such as negative (Holman, Silver, Mogle, & Scott, 2016) or positive (Leist, Ferring, & Filipp, 2010) life events.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, negative life events were associated with both Past Negative and Future Negative in the correlational analysis (see Table 2). This finding possibly reflects that even though an individual's time perspective is considered as fairly stable and traitlike , it may at least to some extent, be modulated by environmental influences, such as negative (Holman, Silver, Mogle, & Scott, 2016) or positive (Leist, Ferring, & Filipp, 2010) life events.…”
Section: Discussionmentioning
confidence: 88%
“…In accord with the theoretical framework behind the ZTPI, we assumed that certain time perspective biases predispose of depressive symptoms, but a reversed direction of influence, from depressive mood state to temporal perspective, might exist (cf. Holman et al, 2016); a model involving a bidirectional influence might possibly be the most accurate. Disentangling the influences requires longitudinal data with repeated measurement of both constructs.…”
Section: Limitationsmentioning
confidence: 99%
“…Research has for instance shown that individual differences in time perspective can predict reactions to traumatic events [9], and that time perspective, and particularly Past Negative, is associated with depression and neuroticism [10]. Recent time perspective research has also underlined the importance of Future Negative, which has been associated with maladaptive coping strategies in late adolescence [11] and negatively associated with well-being among older adults [12].…”
Section: Anxiety Time Perspective and Repetitive Negative Thinkingmentioning
confidence: 99%
“…It can be defined as a set of mainly non-conscious cognitive processes in which continuous flows of experiences are assigned to time frames that help give meaning to those experiences (Keough et al, 1999). It is conceptualised both as a stable personality construct and as subject to change following adversity (Holman et al, 2016;Zimbardo and Boyd, 1999) and different interventions (Boniwell et al, 2014;Korff et al, 2017;Seijts, 1998).…”
Section: Time Perspectivementioning
confidence: 99%